2021
DOI: 10.1007/s11356-021-16489-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications of environmental toxicants on ovarian follicles: how it can adversely affect the female fertility?

Abstract: The pool of primordial follicles formed in the ovaries during early development determines the span and quality of fertility in the reproductive life of a woman. As exposure to occupational and environmental toxicants (ETs) has become inevitable, consequences on female fertility need to be established. This review focuses on the ETs, especially well-studied prototypes of the classes endocrine disrupting chemicals (EDCs), heavy metals, agrochemicals, cigarette smoke, certain chemicals used in plastic, cosmetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 124 publications
0
16
0
Order By: Relevance
“…Persistent environmental pollutants such as PCBs exert a variety of toxic effects in animals, including disturbances of sexual development and reproductive function (He et al, 2021). Reports have shown that ovarian cells exposed to different concentrations of PAHs resulted in ovarian tumor growth and primary ovarian insufficiency (Sumanasekera et al, 2018;Priya et al, 2021). The effects of cadmium, lead, or mercury on the structure and function of reproductive organs have been reviewed in Massányi et al, 2020.…”
Section: The Contribution Of Environmental Pollution To Reproductive ...mentioning
confidence: 99%
“…Persistent environmental pollutants such as PCBs exert a variety of toxic effects in animals, including disturbances of sexual development and reproductive function (He et al, 2021). Reports have shown that ovarian cells exposed to different concentrations of PAHs resulted in ovarian tumor growth and primary ovarian insufficiency (Sumanasekera et al, 2018;Priya et al, 2021). The effects of cadmium, lead, or mercury on the structure and function of reproductive organs have been reviewed in Massányi et al, 2020.…”
Section: The Contribution Of Environmental Pollution To Reproductive ...mentioning
confidence: 99%
“…Although there are multiple factors that play a role, including lifestyle choices in primis , one noteworthy contributor to this decline is an increase in both female and male infertility rates ( 4 ). Increased exposure to man-made environmental pollutants and toxicants, such as endocrine disrupting compounds (EDCs), is known to have negative impacts on reproductive health, thus is suspected to contribute to the increase in infertility rates ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that a number of the compounds act as endocrine-disrupting chemicals (EDCs) with the potential to interfere the hormone systems in human or wild lives ( Schug et al, 2011 ; Dionisio et al, 2015 ). The occupational and environmental exposures of EDCs are strongly correlated with the adverse health outcomes such as reproductive health, development disorders, oncological, immunological and cardiovascular disease, obesity, and neurobehavior disorders ( Elobeid and Allison 2008 ; Yilmaz et al, 2020 ; Boudalia et al, 2021 ; O'Shaughnessy et al, 2021 ; Priya et al, 2021 ). Numerous efforts have been taken to identify that if a compound is endocrine-active or not.…”
Section: Introductionmentioning
confidence: 99%